Advanced Colon Cancer Before the Age of 20 Years: A Case for Extension of the Current Colonscopy Surveillance Guidelines in Hereditary Nonpolyposis Colorectal Cancer Syndrome - Victor K Wong; Eric M Yoshida; Anthony G Ryan; Stephen GF Ho; Baljinder Salh (Canadian Journal of Gastroenterology)
BACKGROUND: Hereditary nonpolyposis colorectal cancer (HNPCC) currently accounts for between 2% to 6% of all colorectal adenocarcinomas. Controversies exist regarding the current guidelines for colonoscopic screening for colon cancer.